PENGELOMPOKAN PERGURUAN TINGGI NEGERI DI INDONESIA MENGGUNAKAN METODE HIRARKI DAN K-MEDOIDS DENGAN UKURAN JARAK MODIFIKASI DATA CAMPURAN - Nabila Puspa Hariani; Kariyam; sekti kartika dini (Asian Journal of Innovation and Entrepreneurship, 2022)
Education is one of the main targets of the government in order to improve the welfare of the people. Higher education is a level of education after secondary education which includes diploma, bachelor, master, specialist, and doctoral education programs. There are several forms of higher education in Indonesia, namely Polytechnics, Colleges, Academics, Universities, and Institutes. Each higher education has university accreditation and study program accreditation. Accreditation is a form of quality and feasibility assessment of higher education institutions or study programs carried out by independent organizations or bodies outside universities. This accreditation can be grouped with other indicators to find out the grouping of State Higher Education in Indonesia in 2020. The grouping is based on accreditation indicators and 8 other indicators are processed using the Complete Linkage and K-Medoids methods. Calculations evaluated using the Shilhouette Coefficient and Davies Bouldin Index (DBI) resulted in optimal clusters of 4 groups using the Complete Linkage method and 2 groups using the K-Medoids method.